Agentes de software em um sistema tutor inteligente de apoio à preparação para a prova de resistência médica - Stefanello, André Luís (2017)
The use of selection tests is becoming more and more present in people's daily lives, both in the professional and academic environments. In this context, one can cite proof of medical residency as a challenge for medical students. According to statistical data, one has the science of the difficulty of solving it, as well as the search for solutions that can help them in the preparation. In this sense, we have sought to create a system with software agents that can contribute or help these students in their studies. To this end, the STIs (Intelligent Tutors Systems) are inserted in this context, which are systems capable of supporting the learning process through autonomous interactions by its software agents. In this perspective, this work arose from the need to demonstrate, in a differentiated way, the content for the study of disciplines involving the five major areas of medicine: Medical Clinic, Pediatrics, Gynecology / Obstetrics, General Surgery and Social Medicine, using agent concepts Software and STIs. For that, the documentation of software requirements was developed, as well as an STI focused on the area of medicine, with four software agents. As a functional software test, data on the functioning of the software agents were collected, tabulated and later presented as graphs. This study demonstrated good results regarding the functioning of software agents, respectively: in Leveling, Allocation, Tutoring and Dueling. Thus, the use of STI developed can facilitate and assist in the evaluation of the performance of students and young physicians, as well as giving teachers a new way of communicating and interacting with students.